ASTRAide: Implementation of Online Learning Platform through Learning Management System and Web-based Integrated Development Environment - Kyle Vincent Faraon (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The development of a Learning Management System (LMS) and a web-based Integrated Development Environment (IDE) was the primary goal of the developers and researchers to aid the College of Computing and Information Technology department of FAITH Colleges in facilitating learning. Instructors using the website could create classes, add lessons and activities, view the progress of the students, comment on their works, and message them. Students, on the other hand, could view the lessons, answer activities, monitor their progress and scores, and most especially, message their professors about their classes. In building the project, the developers used the Agile Development Method to minimize the risks and issues as the development progressed. The survey was conducted to gather information from the possible users of the system. The results revealed that the system was effective and offered different functionalities that could aid both instructors and students in facilitating learning and creating knowledge. The developers and researchers concluded that ASTRAide and its features could provide the needed aid for the CCIT department in teaching young IT professionals.